Bone marrow stromal cell antigen-1 (CD157) regulated by sphingosine kinase 2 mediates kidney fibrosis - Inoue, Tsuyoshi; Nakamura, Yasuna; Tanaka, Shinji; Kohro, Takahide; Li, Lisa X.; Huang, Liping; Yao, Junlan; Kawamura, Suzuka; Inoue, Reiko; Nishi, Hiroshi; Fukaya, Daichi; Uni, Rie; et al. (Frontiers in Medicine, 2022)
Chronic kidney disease is a progressive disease that may lead to end-stage renal disease. Interstitial fibrosis develops as the disease progresses. Therapies that focus on fibrosis to delay or reverse progressive renal failure are limited. We and others showed that sphingosine kinase 2-deficient mice (Sphk2-/-) develop less fibrosis in mouse models of kidney fibrosis. Sphingosine kinase2 (SphK2), one of two sphingosine kinases that produce sphingosine 1-phosphate (S1P), is primarily located in the nucleus. S1P produced by SphK2 inhibits histone deacetylase (HDAC) and changes histone acetylation status, which can lead to altered target gene expression. We hypothesized that Sphk2 epigenetically regulates downstream genes to induce fibrosis, and we performed a comprehensive analysis using the combination of RNA-seq and ChIP-seq. Bst1/CD157 was identified as a gene that is regulated by SphK2 through a change in histone acetylation level, and Bst1-/- mice were found to develop less renal fibrosis after unilateral ischemia-reperfusion injury, a mouse model of kidney fibrosis. Although Bst1 is a cell-surface molecule that has a wide variety of functions through its varied enzymatic activities and downstream intracellular signaling pathways, no studies on the role of Bst1 in kidney diseases have been reported previously. In the current study, we demonstrated that Bst1 is a gene that is regulated by SphK2 through epigenetic change and is critical in kidney fibrosis.